Simulation modeling of recuperative cone unit with ball bearing of road train - Posmetev Valery; Savinkov Maxim; Nikonov Vadim; Posmetev Victor (BIO Web of Conferences)
The ways of increasing the efficiency of tractors aggregated with mounted devices with disk implements during forest restoration activities are determined. A promising design of a recuperative mounted system of a tractor is proposed. A mathematical model is developed that describes the operation of the proposed mounted system during soil cultivation by a tractor. The dependencies of the influence of design and operational factors on the performance indicators of the proposed mounted system are revealed. It is established that with a hydraulic cylinder diameter of 60 mm of the mounted device of a disk implement, the value of the recuperated power reaches 0.55 kW. With an increase in the speed of the tractor, the height and density of obstacles, the intensity of pumping the working fluid into the pneumatic accumulator by the hydraulic cylinder increases, therefore, the recuperated power also increases.